Beverly Thomas
Dec 11, 2020

answers: 1

Register to add an answer

The time for answering the question is over

Answer:

Basic point: If a,b are the roots of an eqn, then (x-a)(x-b)=0 be that quadratic equation.

If x = 2/3, x = -3 are roots, then the eqn will be

(x-2/3)(x-(-3))=0

⇒ (x-2/3)(x+3) = 0

⇒ x²-(2/3)x+3x-2 = 0

⇒ 3x²-2x+9x-6=0

⇒ 3x²+7x-6=0 is the required eqn.

Compare the eqn with ax²+7x+b=0

Therefore, a=3, b= -6

330

Bojka

Dec 11, 2020

For answers need to register.

Contacts

mail@expertinstudy.com

Feedback

Expert in study

About us

For new users

For new experts

Terms and Conditions